Training Internal Medicine Residents in Difficult Diagnosis: A Novel Diagnostic Second Opinion Clinic Experience. (March 2022) - Testa, Stefano; Joshi, Mugdha; Lotfi, Justin; Lin, Bryant; Artandi, Maja; Chiang, Kim F.; Chang, Kevin; Singh, Baldeep; Geng, Linda N.
Background: In primary care clinics, time constraints and lack of exposure to highly complex cases may limit the breadth and depth of learning for internal medicine residents. To address these issues, we piloted a novel experience for residents to evaluate patients with puzzling symptoms referred by another clinician. Objective: To increase internal medicine residents' exposure to patients with perplexing presentations and foster a team-based approach to solving diagnostically challenging cases. Methods: During the academic year 2020–2021, residents participating in their 2-week primary care "block" rotation were given protected time to evaluate 1–2 patients from the Stanford Consultative Medicine clinic, an internist-led diagnostic second opinion service, and present their patients at the case conference. We assessed the educational value of the program with resident surveys including 5-point Lickert scale and open-ended questions. Results: 21 residents participated in the pilot with a survey response rate of 66.6% (14/21). Both the educational value and overall quality of the experience were rated as 4.8 out of 5 (SD 0.4, range 4-5; 1:"very poor"; 5:"excellent"). Residents learned about new diagnostic tools as well as how to approach complex presentations and diagnostic dilemmas. Residents valued the increased time devoted to patient care, the team-based approach to tackling difficult cases, and the intellectual challenge of these cases. Barriers to implementation include patient case volume, time, and faculty engagement. Conclusions: Evaluation of diagnostically challenging cases in a structured format is a highly valuable experience that offers a framework to enhance outpatient training in internal medicine.